2013
DOI: 10.1002/adfm.201203462
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing MOF Mixed Matrix Membranes at the Nanoscale: Towards Structure‐Performance Relationships in CO2/CH4 Separation Over NH2‐MIL‐53(Al)@PI

Abstract: Mixed matrix membranes (MMMs) composed of metal organic framework (MOF) fillers embedded in a polymeric matrix represent a promising alternative for CO2 removal from natural gas and biogas. Here, MMMs based on NH2‐MIL‐53(Al) MOF and polyimide are successfully synthesized with MOF loadings up to 25 wt% and different thicknesses. At 308 K and ΔP = 3 bar, the incorporation of the MOF filler enhances CO2 permeability with respect to membranes based on the neat polymer, while preserving the relatively high separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
164
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(172 citation statements)
references
References 42 publications
2
164
0
1
Order By: Relevance
“…15 -is reported. [341][342][343][344][345] In principle, the lab-scale fabrication procedure of MOF-based MMMs is similar to the one applied for the synthesis of other MMMs. This involves the phase-inversion and solution-casting methods.…”
Section: Mixed Matrix Membranes (Mmms) Made Of Zeolites and Mofsmentioning
confidence: 99%
“…15 -is reported. [341][342][343][344][345] In principle, the lab-scale fabrication procedure of MOF-based MMMs is similar to the one applied for the synthesis of other MMMs. This involves the phase-inversion and solution-casting methods.…”
Section: Mixed Matrix Membranes (Mmms) Made Of Zeolites and Mofsmentioning
confidence: 99%
“…The research group of Gascon prepared mixed matrix membrane (MMMs) based on the NH 2 -MIL-53(Al) MOF material as a promising alternative for CO 2 removal from natural gas. 138 MMMs were produced by dispersing NH 2 -MIL-53(Al), with MOF loadings up to 25 wt% in polyimide, and the final membranes were quantitatively characterized by using tomographic focused ion beam scanning electron microscopy (FIB-SEM, Figure 8). The performance of the NH 2 -MIL-53(Al)-based membranes were investigated in the capture of CO 2 using a CO 2 :CH 4 (1:1) gas mixture ( Figure 9).…”
Section: -Co 2 Capturementioning
confidence: 99%
“…[135][136][137][138][139][140] The Ag@MIL-101 porous material, with different Ag loadings, was prepared by Liu et al 134 via a simple impregnation-reduction methodology immobilizing Ag nanoparticles into the cages of MIL-101(Cr). This material exhibits outstanding bifunctionality: i) on the one hand, Ag@MIL-101 is capable to retain CO 2 in its porous structure; and ii) on the other hand, the CO 2 is converted into compounds with carboxylic acid groups through C-H bond activation of the terminal alkynes.…”
Section: -Co 2 Capturementioning
confidence: 99%
“…2c presents the morphology of grafted-HNTs, showing hollow tubular structure with smooth surfaces that is very similar to Raw-HNTs. Yuan et al [41] observed less distinguished internal wall after APTES modification, which was attributed to APTES filling into the HNTs lumen completely. In comparison, the grafted-HNTs in this work present clear inner wall with hollow cavity, which indicates that APTES modification mainly occurred on the outer surfaces of HNTs.…”
Section: Characterization Of Hntsmentioning
confidence: 99%
“…In particular, the elimination of interface voids between fillers and polymer matrix is crucial to avoid the unselective gas permeation. Tomographic FIB-SEM technique can provide insights of the spatial distribution of fillers, polymer and void space in MMMs [41]. Figure 6 shows the typical 3D surface-rendered view of the HNTs and void volume in etched-HNTs MMM.…”
Section: Characterization Of Mixed Matrix Membranesmentioning
confidence: 99%